A review on the case studies of using the model of human occupation - Pauline Cheung; Xavier C. C Fung (Wolters Kluwer Medknow Publications, 2020)
This study aims to understand how a commonly used theory among occupational therapists, the Model of Human Occupation (MOHO), is applied to cases since it was developed. This review used the keywords of "Model of Human Occupation" and "case" to search target articles in three databases: PubMed, PsycINFO, and SCOPUS. Studies were included when the MOHO is adopted in a case with case description. This review included 34 articles with 57 cases: 11 articles published in the 1980s, 13 articles in the 1990s, seven articles in the 2000s, and three articles in the 2010s. These case studies were reported from the United States, Sweden, Germany, Ireland, and Hong Kong. There were 25 cases diagnosed as a mental health problem (including learning disabilities, attention deficit hyperactivity disorder, dementia, schizophrenia, borderline personality disorder, obsessive-compulsive disorder, bipolar disorder, depressive disorder, conduct disorder, substance abuse, and atypical dissociative disorder); 22 cases were diagnosed as having physical health problems, including musculoskeletal pain, hemiplegia, hand dysfunction, stroke, diabetes, HIV infection, chronic fatigue syndrome, and brain injury; eight cases were diagnosed as having both physical and mental health problems. Most studies reported a treatment plan and left five cases with a mental health problem, and two with a physical health problem did not report any treatment plan. All the studies showed that MOHO can improve the health of the cases and assist them to achieve their goal, except for a case with musculoskeletal problem and two cases with multiple mental disorders. In conclusion, this review showed that MOHO is effective for both physical and mental health problems over the years.